Human-malayan Sun Bear Conflicts in Manipur State, India - Chauhan, N. P. S.; Sethy, Janmejay (Indian Forester, 2011)
A survey in the Manipur state, India was carried out to study the humau-Malayau sun bear (Helarctos malayanus) conflict during 2007-2008. Information on humau casualties was collected by conducting informal interview of the tribal people in raudomly selected villages in Chaudel aud Ukhrul districts. In total, there were 98 humau injury cases by sun bear during 1995-2008. Males were attacked more (87.75%) thau females (12.24%). Injuries were caused to face, nose, eyes, neck, haud aud legs. Bear attacks were recorded in all the seasons, but maximum cases occurred during autumn aud winter months. During March, April, November aud December, 7.14 %, 15.30 %, 19.38 % aud 18.36 % casualties respectively occurred. Out of 98 cases, victims were mainly in the age group of 21-30 years (35.29 %), followed by 31-40 years (35.29 %), aud 41-50 years (22.35 %). Bear accounted for only 1.17 %, 3.52 % aud 2.35 % cases in the age group of 10-20 years, 51-60 years aud 61-70 years respectively. Information on sun bear attacks on humau beings aud circumstances are presented aud discussed. Maximum cases i.e. 63 (66.3 %) occurred in forests, followed by 17 (17.34 %) cases in crop fields aud 18 (18.36 %) cases in the vicinity of villages.